The competency of the dictionaries compiled in jaffna: the 19th century efforts - Gayathree, S. (University of Jaffna, 2016)
Sustainable regional development requires emerging knowledge in Science, Technology, Arts and other fields. Translation plays a vital role with the march of time in order to be familiar with the latest developments and to cope with the dissemination of knowledge. Among all types of translation tools, dictionary is the most essential, prominent and very much supportive tool for translators. Valuable information and vital facts in dictionaries serve as a treasure trove for translators. The 19th century had been a period of vigorous translation activities in the Tamil world. With the advent of Westerners the present form of dictionaries was introduced in the Tamil milieu. Western scholars with the assistance of the native scholars involved themselves in the noble task of compiling authoritative dictionaries as the potential tool for translation. Translation may be enriched and embellished by employing the proper tool from the same milieu. This research aims at analysing the competency of the dictionaries, compiled in Jaffna in the 19th century, for Translation and this is based on descriptive and comparative methodologies. Especially the dictionaries compiled in Jaffna are taken into consideration in this study. The period of this research is limited to the 19th century. This research may facilitate translators by introducing the dictionaries, compiled in Jaffna
Keywords: Translation tools; Tamil milieu; Authoritative Dictionaries